2015
DOI: 10.1007/s00003-015-0933-0
|View full text |Cite
|
Sign up to set email alerts
|

The content of cadmium and lead in canned fish available in the Polish market

Abstract: The study aimed to verify whether canned fish available in Poland were safe in terms of Cd and Pb content. The content of Cd and Pb was examined in 25 products using Graphite Furnace Atomic Absorption Spectrometry (GFAAS). The examined canned fish contained from nearly 0.2 to 1.7 lg Cd and from ca. 0.02 lg to ca. 7.9 lg per 100 g of the product. The content of both Cd and Pb was found to be higher in canned salmon and tuna. It was found that consumption of canned fish acute posed no hazard to adult men. Consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“… a EWI—estimated weekly intake calculated on the basis of the real mean weekly consumption of fishery products and mean level of Cd and Pb b EWI(r)—estimated weekly intake calculated on the basis of the recommended weekly consumption of fishery products and mean level of Cd and Pb c This study d Based on [17] e Based on [16] f Mean body weight was assumed as 70 kg g TWI—2.5 μg Cd per kg of body weight per week [4] h BMDL 01 —10.5 μg Pb per kg of body weight per week [5] i BMDL 10 —4.4 μg Pb per kg of body weight per week [5]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… a EWI—estimated weekly intake calculated on the basis of the real mean weekly consumption of fishery products and mean level of Cd and Pb b EWI(r)—estimated weekly intake calculated on the basis of the recommended weekly consumption of fishery products and mean level of Cd and Pb c This study d Based on [17] e Based on [16] f Mean body weight was assumed as 70 kg g TWI—2.5 μg Cd per kg of body weight per week [4] h BMDL 01 —10.5 μg Pb per kg of body weight per week [5] i BMDL 10 —4.4 μg Pb per kg of body weight per week [5]…”
Section: Resultsmentioning
confidence: 99%
“…Adult Poles weighing 70 kg consume only 0.55% TWI Cd and Pb in the amount of 0.6% BMDL 01 and 1.5% BMDL 10 with the analysed products. Previous studies carried out in our team revealed that more than 94% of adult men regularly consumed canned fish, of which 33% ate it at least once a week [17]. Assuming that adult Poles consume a maximum of one tin of fish a week, they consume 0.8% TWI Cd and 1.23% BMDL 01 and 3.5% BMDL 10 Pb [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of cadmium and lead in Norwegian farmed Atlantic salmon mostly were <LOQ. In Polish retail, canned samples from salmon (4 samples) contained levels of cadmium (1-2 µg/100 g) and lead (6-8 µg/100 g), which was considered safe (Winiarska-Mieczan et al, 2015a). In contrast, mercury and arsenic were detected in almost all samples (Kelly et al, 2008).…”
Section: Heavy Metalsmentioning
confidence: 99%
“…Heavy metals due to canning of products (Winiarska-Mieczan et al, 2015b) aimed to verify whether canned tuna and salmon available in Poland was safe in terms of cadmium and lead content, using Graphite Furnace Atomic Absorption Spectrometry (GFAAS). Although they found that levels of these toxic metals in canned fish did not exceed safe levels for men, they also concluded that there is a lack of data related to heavy metals in canned foods and more research is needed on this topic.…”
Section: Processingmentioning
confidence: 99%